2012
DOI: 10.1111/j.1745-4514.2012.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL COMPOSITION OF THE ESSENTIAL OIL OFMENTHA SPICATAL. FROM TUNISIA AND ITS BIOLOGICAL ACTIVITIES

Abstract: In the present investigation, essential oil (EO) and methanolic extract of Tunisian Mentha spicata leaves were tested for their chemical composition and biological activities. Results showed that EO was characterized by the predominance of oxygenated monoterpenes (92.18%), followed by monoterpene hydrocarbons and sesquiterpenes whose respective amounts were 2.74 and 3.1% of the whole EO. The main volatile compound of M. spicata EO was L‐menthone, accounting for 32.74% of the total volatiles, followed by pulego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
1
27
1
1
Order By: Relevance
“…The IC5 0 values obtained are in agreement with those reported in other studies. Dhifi, Jelali, Mnif, Litaiem, & Hamdi (2013) stated that IC 50 of the essential oils of M. spicata grown in Tunisia was about 10μg/mL (DPPH assay), being in agreement with the present findings. Essential oils compounds such as phenylpropanoids, monoterpenes, and oxygenated sesquiterpenes are capable to inhibit oxidation (Ouerghemmi et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The IC5 0 values obtained are in agreement with those reported in other studies. Dhifi, Jelali, Mnif, Litaiem, & Hamdi (2013) stated that IC 50 of the essential oils of M. spicata grown in Tunisia was about 10μg/mL (DPPH assay), being in agreement with the present findings. Essential oils compounds such as phenylpropanoids, monoterpenes, and oxygenated sesquiterpenes are capable to inhibit oxidation (Ouerghemmi et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The IC 50 obtained in our study is superior to those cited by Snoussi et al 5 with a value of 3.08 ± 0.07µg / ml, Hussain et al 18 showed the IC 50 value of 13.3 ± 0.6 µg/ml, and Dhifi et al 27 (10 ± 0.24 µg / ml) but much lower than those registered by Brahmi et al 7 , Moldovan et al 32 , Allali et al 16 , Soni and Sosa 33 , Ebrahimzadeh et al 34 and Nickavar et. al.…”
Section: Resultscontrasting
confidence: 32%
“…17 M. spicata growing in other countries also contains carvone as one of the major components of its essential oil, e.g., Portugual (41.1%) 22 , Morocco (29.0%) 26 , Bangladesh (73.29%) 20 and Serbia (49.52%). 15 Nevertheless, Dhifi et al 27 24 Other explanation for the differences in oil content and composition may be attributed to factors related to ecotype, phenophases, temperature, relative humidity, photoperiod, irradiance, genotype, and agronomic conditions (harvesting time, plant age, crop density). 5 In addition, the duration of sunshine, the movement of air and precipitation can play roles in the difference in composition of essential oils.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar way, Ait-Ouazzou et al [ 179 ] highlighted that M. pulegium essential oil antibacterial activity against S. aureus , L. monocytogenes , S. enteritidis and E. coli was higher than galingale ( Cyperus longus ) and juniper ( Juniperus phoenicea ) . Dhifi et al [ 180 ] also reported that M. spicata essential oil showed high activity against Gram-positive Staphylococcus (S. epidermidis and S. aureus) and Gram-negative Salmonella and E. coli species. Soković et al [ 181 ] found that M. × piperita and M. spicata essential oils were more active against pathogenic bacteria B. subtilis , E. coli , Pseudomonas ( P. mirabilis , P. aeruginosa ), Salmonella ( S. enteritidis , S. typhimurium) and S. aureus spp.…”
Section: Food Preservative Applications Of Genus Mentha mentioning
confidence: 99%